2020
DOI: 10.1002/amp2.10065
|View full text |Cite
|
Sign up to set email alerts
|

Comparing reusable to disposable products: Life cycle analysis metrics

Abstract: This research is to produce the first quantitative evaluation, using global warming potential (GWP, kg CO 2 eq), of all published cradle-to-gate life cycle studies that compare reusable vs single-use products. We seek to determine whether there are consistent and fundamental factors that differentiate disposable and reusable products. A comparative assessment was made of the cradle-to-gate life cycle analyses of all published comparisons of reusable and single-use products from 1990 to 2016. A literature searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Glass was observed to have a greater environmental impact than plastic when comparing reusable cup materials (Almeida et al, 2018;Cottafava et al, 2021). Overall, a review of lifecycle assessments across a range of items concluded that reusable products consistently achieved a lower environmental impact than single-use products over their lifespan (Alshqaqeeq et al, 2020).…”
Section: Disposable and Reusable Cupsmentioning
confidence: 99%
“…Glass was observed to have a greater environmental impact than plastic when comparing reusable cup materials (Almeida et al, 2018;Cottafava et al, 2021). Overall, a review of lifecycle assessments across a range of items concluded that reusable products consistently achieved a lower environmental impact than single-use products over their lifespan (Alshqaqeeq et al, 2020).…”
Section: Disposable and Reusable Cupsmentioning
confidence: 99%